Amanah and umma: Eco-Islam and epistemological diversity in environmental communication - Alhinai, Maryam; Ringer, Ailesha (Frontiers in Communication, 2025)
This paper is a call to research, teach, and collaborate from epistemically diverse, spiritually grounded, and cosmically connected practices. It is an offering from two scholar-friends who demonstrate that amanah (divine trust) and umma (cosmological community) offer another way of knowing and being with the Earth than neoliberal paradigms. Amanah and umma, practices grounded in Eco-Islam, represent a cosmological vision of the world that resonates across indigenous and kinship-in-place epistemologies. Utilizing a reflexive inter-eco-cultural dialogue, interspersed with evidence from Omani ecocultural ecospiritual practices, we articulate amanah and umma, as not only a moral imperative, but an epistemology—an obligation to know, relate, and act in ways that preserve the sacred integrity of Earth.